Expanding the diversity of mucoralean fungi from northern Thailand: novel Backusella species from soil - Hurdeal, Vedprakash G.; Jones, E. B. Gareth; Santiago, André Luiz C. M. De A.; Hyde, Kevin D.; Gentekaki, Eleni (Phytotaxa, 2022)
Backusella is morphologically and phylogenetically related to Mucor. Previously, due to various morphological similarities, distinction between these two genera was difficult and various Backusella species were classified within Mucor. However, in the last decade, with the advent of molecular phylogeny, the phylogenetic placement of the genus and its representative taxa was stabilised. In this study, a Backusella strain was isolated from soil samples in Thailand. A combination of morphology, phylogeny and physiology was used to characterize it. Phylogenetic analyses using the nuclear rDNA internal transcribed spacer (ITS1-5.8S-ITS2) and large subunit ribosomal ribonucleic acid (28S) genetic markers showed that the isolate is sister to Backusella gigacellularis. The new isolate is characterised by the production of simple or sympodially branched sporangiophores bearing a terminal sporangium. Columellae of sporangia are ellipsoidal, oblong to cylindrical, pyriform, and conical, often constricted in the centre. Sporangiola are globose to subglobose, often produced in short sympodially branched sporophores containing 4–8 sporangiospores each. The isolate grows on a relatively narrow temperature range of 15 °C–28 °C. The results of the three approaches indicated the novelty of the species. This is the first record of Backusella in Thailand.